2017
DOI: 10.1542/peds.2016-0963
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Therapy in an Infant for Ventriculoperitoneal Shunt Meningitis

Abstract: Shunt infections are seen in 3% to 20% of patients who have cerebrospinal fluid (CSF) shunts. Although the staphylococcal species are the most common cause of shunt-related infections, Gram-negative bacteria are increasingly reported with higher mortality rates. Tigecycline, a glycylcycline, is not approved for children. But in the era of nosocomial infections due to multidrug-resistant pathogens, it can be the life-saving option. We report an infant with ventriculoperitoneal shunt-related meningitis treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Penetration of tigecycline into the cerebrospinal fluid of patients with uninflamed meninges is minimal and far below the typical minimum inhibitory concentration (MIC) of tigecycline against A. baumannii (Rodvold et al, 2006). Despite low cerebrospinal fluid concentrations of tigecycline relative to the MIC, there are case reports describing successful treatment of MDR meningitis in children (Jaspan et al, 2010;Emiroglu et al, 2017). Colistin or polymyxin B may be needed to treat meningitis due to MDR A. baumannii (Karaiskos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Penetration of tigecycline into the cerebrospinal fluid of patients with uninflamed meninges is minimal and far below the typical minimum inhibitory concentration (MIC) of tigecycline against A. baumannii (Rodvold et al, 2006). Despite low cerebrospinal fluid concentrations of tigecycline relative to the MIC, there are case reports describing successful treatment of MDR meningitis in children (Jaspan et al, 2010;Emiroglu et al, 2017). Colistin or polymyxin B may be needed to treat meningitis due to MDR A. baumannii (Karaiskos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the available data regarding the use of tigecycline in infants and children younger than 8 years derive from small case series collected retrospectively. [3][4][5][6][7]10 Although optimal dosage has not been defined, the usual dose reported in different case series ranged from 1 to 2 mg/kg every 12 hours. 1 In a case report of 12-month old liver transplant recipient with XDR Acinetobacter baumannii bacteremia, it was found that a dose of 1 mg/kg every 12 hours (without loading dose) provided similar drug exposure (area under the curve, AUC) with adult and children aged 8 to 11 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In different case series, the loading dose has been administered in the most pediatric patients but in infant patients it was not generally given. [3][4][5][6][7]10 All patients in this case series were preterm infants, so the loading dose was not given due to the lack of pharmacokinetics and pharmacodynamics analysis in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only 3 pediatric patients with meningitis in the literature who were treated with IV tigecycline. 2,3,6 We present the first case in the literature of IV and IVT administration of tigecycline in a pediatric patient who had XDR K. pneumoniae due to a VP shunt infection.…”
mentioning
confidence: 99%